(untitled) (Research, Society and Development, 2021)
This study aims to analyze aspects that influence the life of hemodialysis patients, highlight the role of nurses in the care provided to patients undergoing hemodialysis treatment and, finally, list the recurrent complications in patients undergoing hemodialysis. The integrative literature review study, in which the inclusion criteria outlined were original and national articles with up to five years of publication. Publications were searched in the following databases: Database in Nursing, Latin American and Caribbean Literature in Health Sciences and Electronic Library Scientific Electronic Library Online. 287 articles were identified among the databases used and 20 selected. The largest number of articles was found in 2016. The region with the highest number of studies used was the Midwest with 50% of publications highlighting studies in the states of Mato Grosso and the Federal District. It is evident that several Brazilian states suffer from chronic kidney disease, making it a public health problem in Brazil and worldwide. However, many individuals are unaware of the disease, making diagnosis difficult, making careful screening necessary for people who have one or more risk factors for CKD.